Effects of physical activity and resilience on emotional and behavioral problems in Chinese adolescent: a chained mediation model - Shi, YiJie; Zhao, Wei; Lipowski, Mariusz (Frontiers in Psychology, 2025)
BackgroundAdolescent emotional and behavioral problems (EBPs) represent a global health challenge, affecting approximately 970 million individuals worldwide (2019). Adolescence constitutes a critical developmental period characterized by heightened vulnerability to body image concerns, interpersonal stressors, and mental health risks. While parenting styles and physical activity (PA) independently influence adolescent psychological outcomes, their synergistic effects through psychological resilience remain inadequately explored, particularly regarding cultural nuances in Chinese parenting practices (e.g., dual interpretations of overprotection) and chained mediation pathways (parenting → PA → resilience → EBPs).ObjectiveThis study examined the chained mediating roles of physical activity and psychological resilience in the relationship between multidimensional parenting styles (emotional warmth, rejection, overprotection) and EBPs among Chinese adolescents, testing pathways informed by family systems theory and bioecological frameworks.Participants and settingA sample of 503 adolescents (51.09% male; SD = 1.41) was recruited through three-stage cluster sampling across Zhuhai, Guangdong, China. Participants were purposively selected from transition grades: elementary (Grades 5–6, ages 10–12) and junior high schools (Grades 7–9, ages 13–15) across 8 institutions (4 key + 4 general schools). Data collection occurred between April-December 2024, with 89.83% retention after excluding incomplete/invalid responses (logical inconsistencies, accelerometer data <3 valid days). No significant demographic differences existed between retained and excluded cases (p > 0.05).MethodsValidated instruments measured: EBPs (Strengths and Difficulties Questionnaire, α = 0.79), parenting styles (EMBU short form: Rejection α = 0.890; Overprotection α = 0.824; Emotional Warmth α = 0.910), resilience (Connor-Davidson Resilience Scale, α = .970), and PA (IPAQ-SF MET-min/week, α = 0.936). Confirmatory factor analysis established measurement models (RMSEA = 0.026, CFI = 0.971, TLI = 0.970). Structural equation modeling with 5,000 bootstrap resamples (PROCESS Model 6) tested three mediation pathways: (1) Parenting → PA → EBPs; (2) Parenting → Resilience → EBPs; (3) Parenting → PA → Resilience → EBPs.ResultsEmotional warmth significantly predicted reduced EBPs through increased PA (B = 0.862, p < 0.001) and resilience (B = 0.571, p < 0.001), with PA demonstrating the strongest independent mediation (effect = 0.544, 95% CI [0.460, 0.629]). Rejection exacerbated EBPs by suppressing PA (B = −0.318, p < 0.001) and resilience (B = −0.294, p < 0.001; total indirect effect = 0.412, CI [0.332, 0.503]). Overprotection influenced EBPs solely through reduced PA (effect = 0.102, CI [0.058, 0.158]), showing no significant resilience association. The full chained mediation (parenting → PA → resilience → EBPs) was significant (effect = 0.075, CI [0.006, 0.145]), accounting for 24.23% of the total effect.